La normatividad de lo mental y el rol de la segunda persona. Tras las huellas de Donald Davidson - Pedace, Karina (2012)
“The Normativity of the Mental and the Role of the Second Person’s Standpoint. On Davidson’s Footsteps”. I offer in this paper an elucidation of the normativity of the mental in terms of the second person’s standpoint, with the hope of opening a conceptual horizon that will allow us to go beyond Donald Davidson. Aiming at this, the paper is structured as follows. In the first part I present Davidson’s original response to the mind/body problem and reconstruct his argument in favour of the irreducibility of mental concepts thesis. In the second part I deal with the feature that the peculiarity of the mental bears in his system, that is, normativity. In the third section I explore and assess the davidsonian treatment of the first, second and third person standpoints with the aim of finally narrowing down my proposal.